PENGEMBANGAN APLIKASI DESKTOP SKINCARE UNTUK REKOMENDASI PRODUK DAN PENJUALAN BERDASARKAN JENIS KULIT - Lontaan, Rolly Junius; Saroinsong, Marshanda; Sumual, Monica; Masengi, Mitchelly; Mamuaja, Tiara (Jurnal Komputer Terapan, 2025)
Skincare products are increasingly used to address various facial skin problems, maintain skin health, and enhance self-confidence. However, the diversity of skin types and the wide range of skincare products available on the market often make it difficult for users to choose the most suitable products. To address this issue, this study developed a desktop-based skincare application equipped with a recommendation system that uses rule-based and weighted scoring methods, implemented using Python and a MySQL database. The recommendation system analyzes users’ skin types and evaluates the compatibility of product ingredients to generate more accurate recommendations. The test results show that the application can provide suitable recommendations for four skin type categories (dry, oily, sensitive, and combination) with a recommendation suitability level of 84% based on user evaluation. In addition, the application offers a product sales feature that facilitates the process from product selection to purchase. Therefore, this application serves as an effective digital solution to help users determine the right skincare products according to their specific skin needs.